Framing the Arctic: Reconsidering Roald Amundsen’s Gjøa Expedition Imagery - Høvik, Ingeborg (Nordlit, 2015)
In 1906 Roald Amundsen’s Gjøa Expedition returned to Norway after three years in the Arctic. The first to complete a Northwest Passage by sea, the expedition also brought back a substantial amount of ethnographic material concerning the Netsilik Inuit, with whom Amundsen and his crew had been in sustained contact during their stay on King William Island in Nunavut between 1903 and 1905. This material included a large number of photographs, forty-two of which were included as illustrations in his expedition narrative, titled Nordvest-passagen and first released in Norwegian in 1907. Focusing on a selection of published and unpublished photographs from Amundsen’s voyage and their interrelationships, this article examines the degree to which the Gjøa Expedition’s use of photography formed part of a planned project that intersected with anthropological concerns and practices of its time. My purpose is further to demonstrate that there is a discernible change in the representation of indigeneity that occurs when particular photographs were selected and then contextually reframed as illustrations in Nordvest-passagen. On the one hand, the extensive body of photographs taken in the field elaborates the close interaction between crew and Inuit recorded in Amundsen’s personal diary and published narrative, testifying to the existence of an active and dynamic contact zone. In this regard, the original photographs could arguably be read as a dialogic portrayal of the unique individuals Amundsen’s crew met while in the Arctic. On the other hand, a peculiar distancing seems to have taken place as the Gjøa Expedition’s photographs were selected and reproduced as illustrations for Amundsen’s expedition narrative. Likely connected to a desire to match his expedition narrative to existing scientific visual and literary conventions, this shift suggests Amundsen’s attempts through textual and visual means to deny the Netsilik Inuit’s coevalness.
Keywords: Roald Amundsen; Netsilik Inuit; Indigeneity; Photography; Ethnography; Arctic